Evaluasi Kondisi Sebelum Pandemi dan Saat New Normal terhadap Tingkat Ketahanan Pangan Rumah Tangga di Kelurahan Blimbing, Kota Malang - Adelia Meydina Maharani; Farida Rahmawati (Hasanuddin University, 2021)
This study aims to evaluate the condition of food security before and during the new normal in Meduran Village, Blimbing Village, Malang City. The population in this study were all people in Meduran Village with a sample of 55 people. This study uses purposive sampling technique in sampling. In this study it was found that the income variables before the pandemic and expenditure on food needs had a significant effect on the level of food security for the conditions before the pandemic, while the variables of income before the pandemic, income during the pandemic, and income during the new normal also had a significant effect on the level of food security for the current conditions. new normal in Meduran Village. The variables for the number of family members and the age of the respondents did not have a significant effect on the level of food security in Meduran Village. The results of this study require further recommendations from relevant stakeholders.